TEKNOLOGI BLOCKCHAIN PADA PEMASARAN DIGITAL - Ali Syah Putra; Errie Margery; Lusiah Lusiah (Jurnal Mahkota Bisnis (Makbis), 2026)
The modern era is characterized by the rapid advancement of innovative technologies and their widespread implementation across various economic activities. Digitalization involves the utilization of numerous specialized devices connected to the Internet that perform specific functions. Within an integrated system, server technologies play a crucial role by enabling the storage and processing of large volumes of information, including structured, semi-structured, and unstructured data, through high computational capabilities. The availability of powerful equipment capable of executing complex mathematical models using extensive datasets has accelerated the development and application of various machine learning algorithms. By employing different machine learning approaches, hidden patterns and relationships can be identified from the available information, allowing the creation of effective management solutions to optimize processes at the micro, macro, and meso levels. The growing volume of information has also increased the need to ensure security for both individual users and large confidential databases. At the current stage of technological development, blockchain technology is widely utilized to maintain information security and prevent data falsification within databases.